Neuronal hemoglobin in mitochondria is reduced by forming a complex with α-synuclein in aging monkey brains - Yang, Weiwei (Oncotarget, 2016)
Neuronal hemoglobin (nHb) plays a critical role in maintaining normal mitochondrial functioning in the brain. However, in aging and Parkinson's disease (PD) brains, mitochondrial nHb levels are greatly reduced in neurons that accumulate α-synuclein (α-syn), suggesting a link between the two proteins. In this study, we demonstrate that α-syn and Hb can form a complex in both brain tissue and peripheral red blood cells (RBCs) in aging cynomolgus monkeys. nHb-α-syn complex levels in the mitochondrial fraction of the striatum decreased with age; this was negatively correlated with levels in the cytoplasmic fraction and in RBCs and was accompanied by a reduction in mitochondrial free nHb. In contrast, no changes in nHb-α-syn complex formation or free nHb levels were detected in the cerebellum. In vitro studies using a cultured dopaminergic cell line showed that intracellular accumulation of α-syn caused an elevation in nHb-α-syn complex levels in both mitochondrial and cytoplasmic fractions as well as a reduction in mitochondrial free nHb. nHb overexpression increased free nHb levels in mitochondria, stabilized mitochondrial membrane potential, and reduced α-syn-induced apoptosis. The above results suggest that α-syn forms a complex with nHb in selected regions of the aging brain, thereby decreasing mitochondrial function and increasing the risk of PD.